Ion chamber magnetic field correction factors measured via microDiamond cross-calibration from a conventional linac to MRI-linac - Begg, Jarrad; Jelen, Urszula; Keall, Paul; Liney, Gary; Holloway, Lois (Frontiers in Physics, 2022)
Magnetic field correction factors are required for performing reference dosimetry on Magnetic Resonance Imaging Linear accelerators (MRI-linacsL). Methods for measuring magnetic field correction factors usually require specialized equipment and expertise. Our work investigated the use of a microDiamond detector to measure dose with across-calibration an ion chamber between a conventional linac and MRI-linacL as a method to calculate measure ion chamber magnetic field correction factors for the MRI-linacL. Ratios of the microDiamond and ion chamber were measured on a conventional linac, parallel MRI-linacL at 0 T, parallel MRI-linacL at 1 T and perpendicular MRI-linacL at 1.5 T. The beam quality dependence of the microdiamond microDiamond was investigated by comparing the measurements on the conventional linac and parallel MRI-linacL at 0 T. The magnetic field dependence of the microDiamond was investigated comparing the measurements on a parallel MRI-linacL at 0 and 1 T. The ion chamber magnetic field correction factors were calculated by comparing the conventional linac and parallel MRI-linacL at 1 T and the conventional linac and perpendicular MRI-linacL at 1.5 T for the parallel and perpendicular factors respectively. The FC65-G and PTW30013 ion chambers were investigated. For a parallel MRI-linacL, with a beam quality of 〖TPR〗_20,10 = 0.632, we measured magnetic field correction factors of 0.988 ± 0.016 (k = 2) and 0.987 ± 0.016 (k = 2) for a FC65-G and PTW30013 respectively, where k is the coverage factor. For a perpendicular MRI-linacL, with a beam quality of 〖TPR〗_20,10 = 0.701, we measured magnetic field correction factors of 0.995 ± 0.020 (k = 2) and 0.983 ± 0.020 (k = 2) for a FC65-G and PTW30013 respectively. The results showed agreement with previously published work which used different approaches. Our work demonstrates the use of a microDiamond to calculate the ion chamber magnetic field correction factor using measurements on a conventional linac and MRI-linacL. The high level of uncertainty in our results means the method at present can only be used for validation of magnetic field correction factors.